Time dependent FLC determination - Comparison of different algorithms to detect the onset of unstable necking before fracture - Hotz, Walter; Merklein, Marion; Kuppert, Andreas; Friebe, Harald; Klein, Markus (Key Engineering Materials, 2013)
The ISO standard 12004-2:2008E for the determination of forming limit curves based on the section method was approved in 2008. About 4 years of measuring experience in different laboratories has shown advantages and weaknesses of the standard and is leading to some minor changes in the specification. In the years from the development of this standard until today a further technical development of the optical measuring devices occurred, so that it is now possible to determine forming limit curves using the time history of the test. This procedure of determination is referred to a time dependent technique and could be the basis of the ISO 12004 part 2 proposal worked out by the work group "Erweiterung FLC ISO 12004" of the German group of the IDDRG. This publication recapitulates existing work which was carried out from the IDDRG work group regarding the determination of forming limit curves for sheet metal materials. On one hand known issues with the current section based approach are discussed and on the other hand it deals with a comparison of different algorithms to determine the FLC from the time history of the Nakajima test using strategies to identify the instant of onset of instable necking. The different time dependent algorithms [1] utilised are automatically selecting the area where necking is leading to fracture and then analyze the time history of such points using the first or the second time derivative of the true major strain, or of the true thinning strain using methods like: correlation coefficient (modified method based on [2]), gliding correlation coefficient, linear best fit (modified method based on [3]) and gliding difference of mean to median. The resulting experimental FLC points are compared with the results from the section technique described in ISO 12004 part 2 and with the maximum strain values measured in each test. Further a large number of forming limit curves were determined and used for a comparison of these different methods to define the most promising time dependent algorithm, which was selected as a suggestion for the working group defining the new proposed ISO standard 12004 part 2. © (2013) Trans Tech Publications.
LFT Import::2019-07-29 (1927)
Keywords: Forming limit curve (FLC); Material characterization; Time depending evaluation methods